Bibliometric analysis of knowledge management articles in the web of science database - Bilge Kural; İlknur Taştan (Trakya Üniversitesi İktisadi ve İdari Bilimler Fakültesi E-Dergi)
The aim of this study is to guide future research by highlighting prominent developments, trends, authors, publications, journals, and concepts in the field of knowledge management within the management and organization literature. In accordance with the research objective, a bibliometric analysis was conducted using the VOSviewer tool on 3,445 knowledge management articles published in the Web of Science database since 2000. The analyses conducted reveal the distribution of publications by years, the identities of productive authors, and the identification of influential articles, countries, and journals. The research also reveals the frequently used keywords in the field and the prominent research topics over by years. One of the most critical findings that will guide future studies in the field is the emergence of topics such as technological innovation, open innovation, environmental dynamism, innovation performance, COVİD-19, digital transformation, business model innovation, green innovation, and knowledge hiding as prominent areas of focus in knowledge management over the past three years.